Social Harmony of Wonokerto Village Society as a Source of Politeness Learning for Elementary School Students - Purnamasari, Fitria; Sukartono; Rahmawati, Fitri Puji; Minsih; Widyasari, Choiriyah (LPPM Undiksha, 2022)
The problem encountered in this study is the lack of politeness character education in students which causes a lack of student politeness. This study aims to describe the form of adherence to the principle of politeness in language that comes from the social harmony of the community which can be used as a source of learning politeness for elementary school students. There are many studies on character education for students, but there are still few that discuss politeness character education through politeness learning resources from the social harmony of the community which is not widely studied by other researchers. This research uses qualitative research. The research design is a case study. The resource persons in this study were village heads, school principals, and teachers. In this study, the data collection techniques used were observation and interview techniques. In this study, researchers used triangulation to test the validity of the data, namely technical triangulation, and source triangulation. This research was conducted using interactive data analysis techniques, namely data collection, data reduction, data presentation, and concluding. The results showed that the language attitude of the people was polite and could be used as a source of learning politeness for elementary school students. The implementation of politeness learning resources that come from the social harmony of the community is obtained from the kenduri tradition, the wedding celebration tradition, and community service.